Serendipitous diagnosis of aortic coarctation by bilateral parvus et tardus renal Doppler flow pattern - Tarzamni, Mohammad Kazem (BioMed Central, 2007)
BACKGROUND: Aorta Coarctation (AC) is uncommon condition that in most adult patients is asymptomatic. Diagnosis of AC is made during routine physical examination by detection of Blood Pressure (BP) difference between arm and leg. AIM: To describe a novel renal artery Doppler flow pattern pathognomonic of aortic coarctation. METHODS: We enrolled 4 consecutive patients referred to renal artery Doppler Ultrasonography (DU) for diagnostic work-up of secondary arterial hypertension. All met the following inclusion criteria: 1) arterial hypertension at age <30 years; 2) referred for renal DU to rule out renovascular hypertension. RESULTS: We found in all 4 patients (age range 10 to 27 years) a bilateral "parvus-tardus" renal Doppler flow pattern. In all, echocardiographic and angiographic work-ups showed aortic coarctation. CONCLUSION: Careful physical examination should be performed in all hypertensive patients. Furthermore, the suspicion of AC can be raised by a bilateral renal arteries "parvus-tardus" Doppler flow pattern in young hypertensive patients screened for secondary hypertension.